(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This paper will examine current research and thoughts on the promises, problems, and future possibilities in modern distance learning, particularly types delivered via electronic means. Challenges arise due to the current situation under this Pandemic, Colleges and Universities in the Philippines, which led them to arrange distance learning to continue providing good and quality education for college students. Students and teachers alike have a hard time with this arrangement due to the availability of technologies, equipment, internet, poor communication, and major changes in a learning environment. Major changes in the mode of education may negatively affect the student’s academic performance, and it is important to know how to react to these. The researchers will examine each of these issues separately. The researchers used a purposive sampling technique, choosing the study’s respondents. Those (30) representatives from Bachelor of Secondary Education 3rd year majoring in Social Studies college students experiencing distance learning firsthand were the study’s purposive sampling. Purposive sampling is based upon various criteria and characteristics, including specialist knowledge of the research, issue or capacity and willingness to participate in this research.